Buddhist idealism and the problem of other minds. Issue 1 (2nd January 2017) - Perrett, Roy W.
ABSTRACT: This essay is concerned with Indian Yogācāra philosophers' treatment of the problem of other minds in the face of a threatened collapse into solipsism suggested by Vasubandhu's epistemological argument for idealism. I discuss the attempts of Dharmakīrti and Ratnakīrti to address this issue, concluding that Dharmakīrti is best seen as addressing the epistemological problem of other minds and Ratnakīrti as addressing the conceptual problem of other minds.